Interlobate esker architecture and related hydrogeological features derived from a combination of high-resolution reflection seismics and refraction tomography, Virttaankangas, southwest Finland - Maries Georgiana; Ahokangas Elina; Mäkinen Joni; Pasanen Antti; Malehmir Allireza (Springer Berlin Heidelberg, 2022)
A novel high-resolution (2–4 m source and receiver spacing) reflection and refraction seismic survey was carried out for aquifer characterization and to confirm the existing depositional model of the interlobate esker of Virttaankangas, which is part of the Säkylänharju-Virttaankangas glaciofluvial esker-chain complex in southwest Finland. The interlobate esker complex hosting the managed aquifer recharge (MAR) plant is the source of the entire water supply for the city of Turku and its surrounding municipalities. An accurate delineation of the aquifer is therefore critical for long-term MAR planning and sustainable use of the esker resources. Moreover, an additional target was to resolve the poorly known stratigraphy of the 70–100-m-thick glacial deposits overlying a zone of fractured bedrock. Bedrock surface as well as fracture zones were confirmed through combined reflection seismic and refraction tomography results and further validated against existing borehole information. The high-resolution seismic data proved successful in accurately delineating the esker cores and revealing complex stratigraphy from fan lobes to kettle holes, providing valuable information for potential new pumping wells. This study illustrates the potential of geophysical methods for fast and cost-effective esker studies, in particular the digital-based landstreamer and its combination with geophone-based wireless recorders, where the cover sediments are reasonably thick.